Analysis of the Growth Response of Cassava Plants (Manihot Esculenta) to Variability in Water Availability - Novrimansyah, Eko Abadi (International Journal of Multidisciplinary Approach Research and Science, 2024)
In recent decades, there has been a very pronounced climate change on earth. Reduced rainfall and the occurrence of long droughts are direct impacts that can trigger other problems in the agricultural sector such as crop failure and weakening food security. This will also have an impact on the process of growth and agricultural production in the Lampung Province area, especially on cassava plants. Water often limits the growth and development of cultivated plants. The response of plants to lack of water can be seen in their metabolic activity, morphology, growth rate, or productivity. Cell growth is the function of plants that are most sensitive to water shortages. Lack of water will affect cell turgor so that it will reduce cell development, protein synthesis, and cell wall synthesis. The cassava clones used in this study were Garuda Clones with 5 treatment levels, namely the first treatment (P1) 0L, the second treatment (P2) 0.5L, the third treatment (P3) 1L, the fourth treatment (P4) 1.5L, the fifth treatment (P5) 2L. The result of this study is that there is a cassava growth response to water availability in each treatment except for the variable number of shoots. In the variable plant height, significant response variations are obtained, and it is known that the availability of water needed is directly proportional to the response to plant height growth that also increases.